Christianity in Africa: The cost of loyalty to Zionism - Momberg, Marthie (HTS teologiese studies, 2023)
For Israel, the demographic significance of Christians in sub-Saharan Africa presents an opportunity to exchange development aid, trade deals and military agreements for votes in global forums. In this article, the author examines the idea of Israel as a trustworthy diplomatic partner of African countries by considering the impact of Zionism on Christian views. The author drew on media articles for examples of initiatives with African countries, and on reports, calls and minutes of global bodies to reflect on ecclesial and spiritual identities. In contrast to the prevailing perception among Christians in Africa, Zionism cannot be associated with liberation theology. Loyalty to Zionism undermines indigenous spiritual notions, the ideal of an authentic African identity, and Christianity itself. There is an urgent need for theological schools, church leaders and clergy to familiarise themselves with the reality and take the lead in critically assessing and reviewing any hermeneutics and beliefs that inform support for Zionism.Contribution: This article highlights the threat of Israel’s diplomacy in Africa to religious identity, integrity and freedom. As an interdisciplinary, contextual contribution to the sociology of religion, it reveals that loyalty to Israel, a Zionist State, jeopardises Christ’s message of inclusive compassion, justice and equality.